Purification and characterization of bacteriocin produced by Lactobacillus reuteri af182723, a strain isolated from traditionally prepared curd - Keerthini Srikantha; Kapilan, R.; Vasantharuba Seevaratnam (University of Jaffna, 2019)
Bacteriocins are antimicrobial peptides produced by diverse bacterial species that inhibit or kill other microorganisms. In the food industry bacteriocins have potential application as preservative. The bacteriocin obtained from fermented broth in a crude form that may contain lactic acid, acetic acid, H2O2 and other antimicrobial substances. Therefore, the objectives of the study were to purify the bacteriocin and to reveal the possibility of purified compound as biopreservative. Crude bacteriocin was produced by Lactobacillus reuteri AF182723 isolated from traditionally prepared curd in liquid fermentation system. When the crude bacteriocin was purified by sequential three step procedure involving ammonium sulfate fractional precipitation, cation exchange (SP Sepharose) chromatography and size exclusion (Sephadex G-100 column) chromatography, the specific activity (AU/mg) of the bacteriocin increased in each step of purification and it reached 6349.2AU/mg finally from 262.3 AU/mg with the purification fold of 24.206. When the purified bacteriocin was subjected to different temperature and pH treatments, it found stable over wide temperature range (45ºC - 75ºC) and pH range (3-7). When exposed to different enzymes, the purified bacteriocin showed resistant to catalase and amylase enzymes, but showed significantly higher sensitive to pepsin and proteinase K indicating that the antimicrobial substance was proteinaceous in nature. This study concluded that bacteriocin produced by Lactobacillus reuteri AF182723 could be used as a potential food biopreservative. Further safety studies should be done to recommend this potential bacteriocin as food biopreservative.
Keywords: Bacteriocin; Characterization; Lactobacillus reuteri AF182723; Purification